Juventude e mercado de trabalho: uma análise do perfil das políticas de emprego no Brasil no período de 2003 a 2019. - OLIVEIRA, Amarayna Minelly Sousa (2021)
Study on the profile of employment policies aimed at youth from 2003 to 2019. The issue of unemployment affecting youth and its ways of coping in Brazil is analyzed, recovering important points about the job market and unemployment, in how has been incorporated into the youth workforce over the years, and what kind of employment policies have been formulated to address this issue. It analyzes the determinations of youth unemployment in the current stage of the development of capitalism, bringing a conceptual approach and classification of youth, accompanied by an analysis of how changes in the world of work have implications for the insertion of young people in the contemporary labor market. It configures and scales the reality of youth unemployment in Brazil, showing how changes in the labor market, accompanied by high unemployment rates, brought particularities inherent to youth unemployment, especially those from low-income families. It analyzes the profile assumed by public policies aimed at the insertion of youth in the labor market in Brazil from 2003 to 2019, in which they appear, as a means to try to reverse this scenario. With the high rates of unemployment, disintegration and precariousness of work and the limited offer of opportunities, the issue of work is one of the great concerns of youth and it is also so in the field of employment policies. Some considerations are made that allowed us to conclude that young people are one of the groups that present difficulties in entering the labor market, especially in the context of a more flexible structure, where new trends intensify the youth unemployment crisis.